2002
DOI: 10.1161/hc0402.102621
|View full text |Cite
|
Sign up to set email alerts
|

Stromelysin-1 (Matrix Metalloproteinase-3) and Tissue Inhibitor of Metalloproteinase-3 Are Overexpressed in the Wall of Abdominal Aortic Aneurysms

Abstract: Background-Atherosclerosis is implicated in the pathogenesis of abdominal aortic aneurysm (AAA) but more often causes aortic occlusive disease (AOD). The matrix metalloproteinases (MMPs) degrade extracellular matrix and may play a central role in the pathogenesis of AAA. The aim of this study was to examine differences in the patterns of MMP and MMP inhibitor expression between AAA and AOD. Methods and Results-The expression of mRNA for 14 MMPs and 4 tissue inhibitors of metalloproteinases (TIMPs) was estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
95
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(101 citation statements)
references
References 36 publications
2
95
0
4
Order By: Relevance
“…The observed differences could not be attributed to a particular cardiovascular risk factor because the presence of dyslipidemia, arterial hypertension, diabetes and smoking, were similar between both groups. There are conflicting reports on the expression of MMPs in relation to aneurysms [7][8][9][10], but in general, the majority of the studies have reported the involvement of at least MMP-2 and MMP-9 in abdominal aortic aneurysms [24]. A novel finding of our study was an increased expression of MMP-1 and-3, but not MMP-9 in femoral aneurysms, suggesting that regional differences in the proteolytic mechanisms may be operating in different arterial beds.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…The observed differences could not be attributed to a particular cardiovascular risk factor because the presence of dyslipidemia, arterial hypertension, diabetes and smoking, were similar between both groups. There are conflicting reports on the expression of MMPs in relation to aneurysms [7][8][9][10], but in general, the majority of the studies have reported the involvement of at least MMP-2 and MMP-9 in abdominal aortic aneurysms [24]. A novel finding of our study was an increased expression of MMP-1 and-3, but not MMP-9 in femoral aneurysms, suggesting that regional differences in the proteolytic mechanisms may be operating in different arterial beds.…”
Section: Discussionmentioning
confidence: 48%
“…MMP-1 has been related to cardiac hypertrophy, dilation and systolic dysfunction in the hearts of transgenic mice [25]. On the other hand, MMP-3 would contribute to plaque destabilization by degrading ECM components, and could also promote aneurysm formation by degrading the elastic lamina [9]. These effects may be directly mediated by MMP-3 or by activation of other proMMPs [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Increased MMP-9 levels were detected in plasma of AAA patients and patients with acute coronary syndromes. 2,3 In addition, aneurysm and atherosclerotic tissues overexpress MMP-1, -2, -3, -7, -8, -9, -12, -13, -14, and -17 (Carrell et al 4 and references therein).…”
mentioning
confidence: 99%
“…Among these, an important role was attributed to MMPs [1,2,19,23,24] that determine, in response to biochemical and local hemodynamic insults, abnormal extracellular matrix degradation promoting an exuberant expansive remodeling of the vascular wall and thus the development of CAE [25].…”
Section: Discussion:-mentioning
confidence: 99%